PEMBANDARAN KOLONIAL & PENGHAPUSAN BANGSA MELAYU DI MALAYSIA - Norsaleha Mohd Salleh; Mohd Zul Fahmi Md Bahrudin; Nur Hanis Mohamad Noor (Interdisciplinary Research and International Strategy (IRIS) Institute Berhad, 2021)
History of colonial urbanization in Malaysia